Osteonecrosis After Femoral Neck Fractures in Children and Adolescents: Analysis of Risk Factors. Issue 2 (March 2016) - Spence, David; DiMauro, Jon-Paul; Miller, Patricia E.; Glotzbecker, Michael P.; Hedequist, Daniel J.; Shore, Benjamin J.
Abstract : Background: The most serious complication of femoral neck fractures in children and adolescents is osteonecrosis. Although a number of factors have been implicated in the development of osteonecrosis, no specific cause-and-effect relationship has been determined. The primary purpose of this study was to determine the prevalence of osteonecrosis in children and adolescents after femoral neck fractures and to identify risk factors for its development. Methods: This retrospective review identified 70 patients between the ages of 1.3 and 18.1 years who were treated for a femoral neck fracture between 2000 and 2011 at a single level I pediatric trauma center and followed until clinical and radiographic union. Demographic information, injury event details, type of surgical treatment, associated injuries, time from injury to treatment, and postoperative alignment were recorded from chart and radiographic review. The primary outcome was the presence of osteonecrosis, which was determined by review of available imaging. Multivariable logistic regression analysis tested age, time to treatment, type of fixation, mechanism of injury, postoperative alignment, and capsular decompression as possible risk factors for the development of osteonecrosis. Results: Osteonecrosis occurred in 20 (29%) of the 70 patients. The median time to diagnosis of osteonecrosis was 7.8 months. Multivariable predictors of osteonecrosis included fracture displacement ( P =0.01) and fracture location ( P =0.02). Patient age, type of fixation, mechanism of injury, capsular decompression, postoperative alignment, and performance of reduction were not predictive of osteonecrosis after femoral neck fracture. Finally, time to treatment also was found to be a positive predictor of osteonecrosis ( P =0.004), with osteonecrosis more likely in patients treated in less than 24 hours, but this finding is likely due to confounding because injury severity was closely linked to time to treatment. Conclusions: Regardless of the treatment, the prevalence of osteonecrosis after femoral neck fractures remains high. Recognizing factors that are predictive of the development of osteonecrosis can help surgeons counsel patients and families appropriately about the risk of this complication. Level of Evidence: Therapeutic Level III—retrospective comparative study.